Literatur Review: Media Sosial dan Implikasi Terhadap Pola Pikir Peserta Didik Sekolah Menengah Atas - Rahman Yusuf; Dita Septasari (Jurnal Pendidikan Teknologi Informasi (J-Diteksi), 2026)
Social media has transformed into a digital ecosystem inseparable from the lives of Senior High School (SMA) students, bringing complex implications for the development of their thinking patterns. This literature review aims to analyze and synthesize current empirical evidence regarding the impact of social media on various domains of high school students' thinking patterns, encompassing cognitive, socio-emotional, and academic aspects. The method employed is a literature review of 15 research articles from various international databases and accredited national journals. The analysis reveals that excessive social media use correlates with attention disorders, decreased working memory, and erosion of students' intrinsic learning motivation. In the socio-emotional domain, passive usage patterns accompanied by social comparison contribute to increased anxiety, depressive symptoms, and decreased socio- emotional skills. Nevertheless, research also uncovers the positive potential of social media when used purposefully for collaborative learning. Key moderating factors determining the impact of social media use are students' self-regulation abilities and intrinsic motivation. Referring to the complexity of these impacts, this review recommends the integration of Critical Digital Literacy into the curriculum as a fundamental strategy for building digital resilience. Critical Digital Literacy equips students with a critical thinking framework to analyze content, understand platform mechanisms, manage online identity reflectively, and utilize technology constructively. Thus, high school students can become intelligent, critical, and responsible users within their digital ecosystem.